Negative electrode active material and secondary battery

By using Si nanoparticles or silicon oxide particles to embed carbonaceously in the negative electrode active substance of the secondary battery and optimizing relevant parameters, the problem of volume expansion and contraction during charging and discharging is solved, and the initial Coulomb efficiency and battery performance stability are improved.

CN119790508AInactive Publication Date: 2025-04-08DIC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380062237.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-01
Filing Date
2023-06-29
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The negative electrode active substance of existing secondary batteries expands and contracts during charging and discharging, resulting in unstable performance, and the initial Coulomb efficiency is low.

Method used

The negative electrode active material embedded in Si nanoparticles or silicon oxide particles and carbonaceous phase is used to optimize electron conductivity and structural stability by controlling the surface spacing of the carbon 002 surface, the thermal weight reduction rate, weight increase starting temperature and porosity.

Benefits of technology

The initial Coulomb efficiency and battery characteristics of the secondary battery are significantly improved, the capacitance loss of Si nanoparticles is suppressed, and the circulation durability of the negative electrode active material is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005287163060000031
    Figure BDA0005287163060000031
  • Figure BDA0005287163060000111
    Figure BDA0005287163060000111
  • Figure BDA0005287163060000261
    Figure BDA0005287163060000261
Patent Text Reader

Abstract

Provided are: a negative electrode active material which provides a secondary battery having high initial coulombic efficiency, which is one of the important properties of the secondary battery; and a secondary battery which contains the negative electrode active material and has high initial efficiency. A negative electrode active material containing Si nanoparticles and / or silicon oxide particles and a carbonaceous phase, the carbonaceous phase embedding the Si nanoparticles and / or the silicon oxide particles, and the interplanar spacing of the carbon 002 plane in the carbonaceous phase as determined by XRD measurement being 0.340 nm to 0.38 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a negative electrode active material and a secondary battery comprising the negative electrode active material. Background Art

[0002] Non-aqueous electrolyte secondary batteries are used in portable devices, hybrid vehicles, electric vehicles, household storage batteries, and the like, and are required to have a plurality of characteristics such as electric capacity, safety, and operational stability in a balanced manner.

[0003] As such secondary batteries, lithium-ion batteries using lithium-intercalation compounds that release lithium ions from the interlayer as negative electrode materials are mainly known. For example, various lithium-ion batteries using carbonaceous materials such as graphite that can absorb and release lithium ions between the interlayers between crystal planes during charge and discharge as negative electrode active materials are being developed and put into practical use.

[0004] Furthermore, in recent years, with the miniaturization of various electronic devices and communication devices and the rapid popularization of hybrid vehicles, etc., there is a strong demand for the development of secondary batteries with higher capacity and further improved various battery characteristics such as cycle characteristics and discharge rate characteristics as driving power sources for these devices.

[0005] As one of the attempts to improve the performance of secondary batteries, a negative electrode active material for a non-aqueous electrolyte secondary battery having a silicon compound represented by the general formula SiOx is described (for example, Patent Document 1). The negative electrode active material particles described in Patent Document 1 have excellent electrical conductivity by coating at least a portion of the surface of the aforementioned silicon compound with a carbon film. Furthermore, it is believed that by setting the specific surface area of ​​the carbon film to a specific range, the impregnation of the electrolyte of the battery becomes good, and by setting the compression resistivity of the carbon film to a specific range, the conductivity of the surface of the negative electrode active material particles becomes sufficient, and it is not easy to cause the micro-precipitation of Li caused by the concentration of power on the surface.

[0006] On the other hand, attempts have also been made to improve the performance of secondary batteries by using a negative electrode active material containing silicon particles (for example, Patent Documents 2 to 4).

[0007] Patent document 2 describes a negative electrode material for a battery, which includes a silicon material region and a carbon material region formed by separating a gap around at least a portion of the silicon material region, and the (002) average plane spacing d002 of the carbon material region obtained by powder X-ray diffraction using Cu-Kα rays is greater than 0.365nm and less than 0.390nm. It is recorded that the expansion and contraction of silicon during charge and discharge can be efficiently suppressed by the structure of patent document 2, and a secondary battery with improved specific capacity and cycle durability can be obtained.

[0008] Patent document 3 discloses a negative electrode active material for a lithium ion secondary battery, which comprises flaky silicon nanoparticles and a silicon-based inorganic compound, wherein the silicon-based inorganic compound encapsulates the flaky silicon nanoparticles and has a bonding structural unit belonging to SiC4. 29 Si-NMR peaks are present, and the equivalent composition ratio is within a specific range. It is described that the charge and discharge characteristics of the obtained secondary battery are improved.

[0009] Patent Document 4 discloses a core-shell composite particle, in which a carbon matrix having silicon particles enclosed in pores having a specific diameter is used as a core, and a non-porous shell based on amorphous carbon is used as a shell. It is recorded that the obtained secondary battery exhibits high coulombic efficiency and more stable electrochemical behavior in subsequent cycles.

[0010] Prior art literature

[0011] Patent Literature

[0012] Patent Document 1: Japanese Patent Application Publication No. 2016-164870

[0013] Patent Document 2: Japanese Patent Application Publication No. 2019-125435

[0014] Patent Document 3: Japanese Patent Application Publication No. 2021-114483

[0015] Patent Document 4: Japanese Patent No. 6523484 Summary of the invention

[0016] Problems to be solved by the invention

[0017] As described above, attempts have been made to improve the performance of secondary batteries by making various improvements to negative electrode active materials containing silicon or silicon compounds.

[0018] However, the performance of the obtained secondary batteries is still not sufficient, and further improvement of the negative electrode active material is required.

[0019] The present inventors focused on Si nanoparticles or silicon oxide particles and the carbonaceous phase that embeds them, and conducted various studies for the purpose of efficiently suppressing the volume expansion and contraction of Si accompanying charge and discharge and improving the electronic conductivity of the negative electrode active material, thereby completing the present invention.

[0020] That is, an object of the present invention is to provide a negative electrode active material for a secondary battery that provides a large capacity per unit weight and excellent initial coulombic efficiency, which are important properties of a secondary battery.

[0021] Means for solving problems

[0022] The present invention has the following aspects. [1]

[0024] A negative electrode active material, comprising at least one of Si nanoparticles or silicon oxide particles and a carbonaceous phase, wherein the carbonaceous phase embeds at least one of the Si nanoparticles or silicon oxide particles, and the interplanar spacing of the carbon 002 planes in the carbonaceous phase determined by XRD measurement is 0.34nm to 0.38nm. [2]

[0026] The negative electrode active material according to the above [1], wherein the mass reduction rate at 100 to 800° C. obtained by TG analysis under dry air flow is 10 to 70%. [3]

[0028] The negative electrode active material according to [1] or [2], wherein the weight increase start temperature obtained by TG analysis under dry air flow is 550° C. or higher. [4]

[0030] The negative electrode active material according to any one of [1] to [3] above, comprising 0.1 wt % to 19 wt % of a silicon-based material. [5]

[0032] The negative electrode active material according to any one of [1] to [4], wherein the specific surface area (BET) is 0.01 m 2 / g to 20m 2 / g. [6]

[0034] The negative electrode active material according to any one of [1] to [5] above, wherein the average particle size (D50) is 0.5 μm to 10 μm. [7]

[0036] The negative electrode active material according to any one of [1] to [6], which has a carbon coating, a porosity defined by the following formula (1) of 7% or more and 20% or less, and a true density of 1.6 g / cm 3 Above and 2.0g / cm 3 the following.

[0037]

[0038] In formula (1), V represents the porosity (%), and ρ represents the density inside the negative electrode active material (g / cm 3 ), ρ' represents the density of the entire negative electrode active material (g / cm 3 ), ρ" represents the density of the carbon film (g / cm 3 ), A represents the amount of carbon film (mass %).

[0039] Furthermore, the present invention has the following aspects. [8]

[0041] A secondary battery comprising the negative electrode active material described in any one of [1] to [7].

[0042] Effects of the Invention

[0043] According to the present invention, there are provided a negative electrode active material for providing a secondary battery having high initial coulombic efficiency, which is one of the important properties of a secondary battery, and an excellent balance of battery characteristics, and a secondary battery having the negative electrode active material. DETAILED DESCRIPTION

[0044] In addition, in the following description, Si represents the same substance as "silicon".

[0045] The negative electrode active material of the present invention (hereinafter also referred to as "the present negative electrode active material") contains at least one of Si nanoparticles or silicon oxide particles and a carbonaceous phase, the carbonaceous phase embeds the Si nanoparticles, and the interplanar spacing of the carbon 002 planes in the carbonaceous phase determined by XRD measurement is 0.34nm to 0.38nm.

[0046] The electrochemical reactions caused by the charge and discharge of secondary batteries are roughly divided into two types. One is the reaction that occurs during charge and discharge, which is the insertion and extraction reaction of lithium ions. The other is the side reaction that occurs on the surface of the solvent, electrolyte and active material in the electrolyte. Since SEI (Solid Electrolyte Interface) is generated due to this side reaction, the initial efficiency of the secondary battery is reduced. It is believed that when the present negative electrode active material is used in a secondary battery, the electrochemical side reactions on the surface of the active material are suppressed, and the initial coulombic efficiency of the secondary battery becomes larger.

[0047] The aforementioned Si nanoparticles are nanoparticles of zero-valent Si. Nanoparticles refer to particles having an average particle size of nanometer-scale particle size, preferably 10nm to 300nm, more preferably 20nm to 250nm, and further preferably 30nm to 200nm. In addition, from the viewpoint of charge and discharge performance and capacity maintenance when made into a negative electrode active material, the average particle size of the Si nanoparticles is preferably 100nm or less, more preferably 70nm or less.

[0048] Here, the average particle size refers to the volume average particle size, which is the value of D50 that can be measured using a laser diffraction particle size analyzer, etc. D50 can be measured by a dynamic light scattering method using a laser particle size analyzer, etc. In the particle size distribution of Si nanoparticles, when a volume cumulative distribution curve is drawn from the small diameter side, it is the particle size at the time of accumulation 50%.

[0049] Large-sized Si nanoparticles exceeding 300 nm become large blocks, and when made into negative electrode active materials, they are prone to pulverization during charge and discharge, so it is expected that there is a tendency for the capacity retention rate of the negative electrode active material to decrease. On the other hand, small-sized Si nanoparticles less than 10 nm are too fine, so the Si nanoparticles are easy to agglomerate with each other. Therefore, the dispersibility of the Si nanoparticles in the negative electrode active material may decrease. In addition, if the Si nanoparticles are too fine, their surface activity energy becomes high, and there is also a tendency for more byproducts to appear on the surface of the Si nanoparticles during the high-temperature calcination of the negative electrode active material. These may lead to a decrease in charge and discharge performance.

[0050] From the above viewpoints, the Si nanoparticles are preferably within the above average particle size range, and the number of Si nanoparticles larger than 300 nm and smaller than 10 nm is as small as possible.

[0051] The Si nanoparticles can be produced by nano-sizing Si blocks by pulverization, etc. The presence of the Si nanoparticles can improve the charge / discharge capacity and initial coulomb efficiency when the negative electrode active material is used as a secondary battery.

[0052] The Si nanoparticles can be obtained, for example, by pulverizing a zero-valent silicon mass into particles such that the average particle size falls within the above range.

[0053] As the pulverizer used for pulverizing Si blocks into nanoparticles, there can be exemplified pulverizers such as ball mills, bead mills, and jet mills. In addition, the pulverization can be wet pulverization using an organic solvent, and as the organic solvent, for example, alcohols, ketones, etc. can be preferably used, and aromatic hydrocarbon solvents such as toluene, xylene, naphthalene, and methylnaphthalene can also be used.

[0054] Si nanoparticles can be obtained by controlling the conditions of the bead mill, such as the bead diameter, blending ratio, rotation speed, or grinding time, and classifying the obtained silicon particles.

[0055] The shape of the Si nanoparticles is not particularly limited. From the perspective of charge-discharge performance when made into a negative electrode active material, the length in the long axis direction is preferably 70 to 300 nm, and the thickness is preferably 15 to 70 nm. From the perspective of charge-discharge performance when made into a negative electrode active material, the ratio of thickness to length, i.e., the so-called aspect ratio, is preferably 0.5 or less.

[0056] Regarding the morphology of Si nanoparticles, the average particle size can be measured by dynamic light scattering, but by using a transmission electron microscope (TEM) and a field emission scanning electron microscope (FE-SEM) analysis method, the sample of the aspect ratio can be more easily and accurately identified. In the case where the present negative electrode active material includes the aforementioned Si nanoparticles, the state of the Si nanoparticles can be identified by cutting the sample with a focused ion beam (FIB) and observing the cross section with FE-SEM, or by slicing the sample and observing it with TEM.

[0057] It should be noted that the aspect ratio of the Si nanoparticles described above is a result of calculation based on 50 particles of the sample present in the main portion of the field of view captured by the TEM image.

[0058] From the viewpoint of capacitance and initial coulombic efficiency, the specific surface area of ​​the Si nanoparticles is preferably 100 m 2 / g to 400m 2 / g.

[0059] From the viewpoint of capacitance and initial coulombic efficiency, the specific surface area of ​​Si nanoparticles is more preferably 100 m 2 / g to 300m 2 / g, more preferably 100m 2 / g to 230m 2 / g.

[0060] The specific surface area is a value obtained by the BET method and can be obtained by nitrogen adsorption measurement, for example, by using a specific surface area measuring device.

[0061] The specific surface area of ​​Si nanoparticles can be measured as follows: That is, the amount of nitrogen adsorption at a relative pressure of 0.5 or less at liquid nitrogen temperature is determined at multiple points, and the specific surface area is calculated from the BET diagram within a range where the adsorption heat C value is positive and linear.

[0062] The shape of Si nanoparticles can be any one of granular, needle-shaped, and thin-flaked, preferably crystalline. In the case where Si nanoparticles are crystalline, from the viewpoint of initial Coulomb efficiency and capacity maintenance rate, it is preferred that the crystallite diameter obtained by the diffraction peak belonging to Si (111) in X-ray diffraction is in the range of 5nm to 14nm. The crystallite diameter is more preferably less than 12nm, and more preferably less than 10nm.

[0063] The silicon oxide particles are generally a general term for amorphous silicon oxide particles obtained by cooling and precipitating silicon monoxide gas generated by heating a mixture of silicon dioxide and metallic silicon, and are represented by the following general formula (1).

[0064] SiOn(1)

[0065] In the above formula (1), n ​​is 0.4 or more and 1.8 or less, and preferably 0.5 or more and 1.6 or less.

[0066] In the case where the present negative electrode active material contains silicon oxide particles, if the average particle size of the silicon oxide particles exceeds 5 μm, the silicon oxide particles become large blocks, and when the present negative electrode active material is used for the negative electrode, the negative electrode active material will expand and shrink significantly due to the silicon oxide particles during charge and discharge. As a result, stress is concentrated in a part of the carbonaceous phase, which easily causes the structure of the negative electrode active material to collapse, and there is a tendency for the capacity retention rate of the negative electrode active material to decrease.

[0067] On the other hand, since the small-sized silicon oxide particles less than 300 nm are too fine, the silicon oxide particles are easy to agglomerate with each other. Therefore, the dispersibility of the silicon oxide particles in the negative electrode active material may be reduced. In addition, if the silicon oxide particles are too fine, their specific surface area becomes higher, and there is also a tendency for more byproducts to form on the surface of the silicon oxide particles during the high-temperature calcination of the negative electrode active material. These may lead to a decrease in charge and discharge performance.

[0068] Therefore, from the above viewpoints, the average particle size of the silicon oxide particles is preferably 3 μm or less, more preferably 2 μm or less. In addition, from the viewpoints of particle dispersibility and specific surface area, the average particle size of the silicon oxide particles is preferably 300 nm or more, more preferably 200 nm or more.

[0069] Here, the average particle size is the value of D50 as in the above. D50 is as described above.

[0070] The silicon oxide particles can be obtained, for example, by pulverizing silicon oxide into particles so that the average particle size falls within the above-mentioned range.

[0071] As the pulverizer used for pulverization, there can be exemplified pulverizers such as ball mill, bead mill, jet mill, etc. In addition, the pulverization can be wet pulverization using an organic solvent, and as the organic solvent, for example, alcohols, ketones, etc. can be preferably used, and aromatic hydrocarbon solvents such as toluene, xylene, naphthalene, methylnaphthalene, etc. can also be used.

[0072] The average particle size of the silicon oxide particles can be adjusted to the above range by controlling the conditions of the bead mill such as the bead particle size, blending ratio, rotation speed, or pulverization time, or by classifying the obtained silicon oxide particles.

[0073] The shape of the silicon oxide particles may be any of granular, needle-like, and flaky.

[0074] Regarding the morphology of silicon oxide particles, the average particle size can be measured by dynamic light scattering, but by using a transmission electron microscope (TEM) or a field emission scanning electron microscope (FE-SEM) analysis method, the sample of the aspect ratio can be more easily and accurately identified. In the case where the negative electrode active material contains the silicon oxide particles, the state of the Si nanoparticles can be identified by cutting the sample with a focused ion beam (FIB) and observing the cross section with FE-SEM, or by slicing the sample and observing it with TEM.

[0075] It should be noted that the aspect ratio of the silicon oxide particles is a result of calculation based on 50 particles of a main part of the sample within the field of view of the TEM image.

[0076] The present negative electrode active material may contain at least one of the Si nanoparticles or the silicon oxide particles, or both. The present negative electrode active material preferably contains both the Si nanoparticles and the silicon oxide particles.

[0077] When the present negative electrode active material contains both the Si nanoparticles and the silicon oxide particles, it is preferred that the Si nanoparticles have silicon oxide on their surfaces from the viewpoint of suppressing initial capacity loss and thus improving initial coulombic efficiency.

[0078] When the surface of the Si nanoparticles has silicon oxide, the surface of the Si nanoparticles is preferably covered with a silicon dioxide film which is a silicon oxide film.

[0079] Examples of the carbonaceous phase of the negative electrode active material include crystalline carbon and amorphous carbon. Examples of crystalline carbon include natural graphite and artificial graphite, and examples of amorphous carbon include graphitizable carbon and non-graphitizable carbon.

[0080] These carbonaceous phases can be appropriately selected from the desired performance according to the purpose. For example, from the viewpoint of the energy density of the secondary battery obtained, crystalline carbon is preferably selected. On the other hand, from the viewpoint of the battery durability caused by the expansion and contraction of the active material accompanying charge and discharge, amorphous carbon is preferably selected.

[0081] From the viewpoint of the initial efficiency of the secondary battery, the carbonaceous phase is preferably amorphous carbon.

[0082] The carbonaceous phase of the present negative electrode active material is embedded with at least one of the aforementioned Si nanoparticles or the aforementioned silicon oxide particles. That is, when the present negative electrode active material contains the aforementioned Si nanoparticles, the carbonaceous phase embeds at least a portion of the aforementioned Si nanoparticles, when the present negative electrode active material contains the aforementioned silicon oxide particles, the carbonaceous phase embeds at least a portion of the aforementioned silicon oxide particles, and when the present negative electrode active material contains the aforementioned Si nanoparticles and the aforementioned silicon oxide particles, the carbonaceous phase embeds at least a portion of the aforementioned Si nanoparticles and the aforementioned silicon oxide particles. Carbonaceous phase embedding refers to the state in which Si nanoparticles or the aforementioned silicon oxide particles are dispersed in the carbonaceous phase. From the perspective of the energy density of the secondary battery obtained, it is preferred that the aforementioned Si nanoparticles or the aforementioned silicon oxide particles are in as close contact with the carbonaceous phase as possible in the present negative electrode active material. The state in which the carbonaceous phase embeds at least one of the aforementioned Si nanoparticles or the aforementioned silicon oxide particles can be observed by using EDS (energy dispersive X-ray spectroscopy) of SEM (scanning electron microscope) to observe the particle cross section and confirmed by using an electron beam probe microanalyzer (EPMA).

[0083] The Si nanoparticles and the carbonaceous phase preferably satisfy the range of porosity described below.

[0084] The total amount of the aforementioned Si nanoparticles or the aforementioned silicon oxide particles and the carbonaceous phase is set to 100 mass%, and the amount of the aforementioned Si nanoparticles or the aforementioned silicon oxide particles in the present negative electrode active material is preferably 5 mass% to 70 mass%, and more preferably 10 mass% to 60 mass%. When the present negative electrode active material contains both the aforementioned Si nanoparticles and the aforementioned silicon oxide particles, it is preferred that the total amount of the aforementioned Si nanoparticles, the aforementioned silicon oxide particles and the carbonaceous phase is 100 mass%, and the total amount of the aforementioned Si nanoparticles and the aforementioned silicon oxide particles is within the aforementioned range. Preferably, most of these aforementioned Si nanoparticles or the aforementioned silicon oxide particles are embedded in the aforementioned carbonaceous phase, and more preferably, more than 60% of the volume ratio of the aforementioned Si nanoparticles or the aforementioned silicon oxide particles as a whole is embedded, and more preferably more than 90%.

[0085] The interplanar spacing of the carbon 002 planes obtained by XRD in the aforementioned carbonaceous phase can be measured as follows. That is, the negative electrode active material containing the carbonaceous phase is filled in the sample holder, and CuKα rays are used as the ray source to obtain an X-ray diffraction pattern. Regarding the peak position of the X-ray diffraction pattern, the peak position is obtained by the 2θ value, the wavelength of the CuKα ray is set to 0.15418nm, and the carbon phase 002 interplanar spacing is calculated by the Bragg formula described below.

[0086] d002=λ / 2·sinθ

[0087] The closer the carbonaceous phase is to the state of graphite, the higher the crystallinity is, and the closer the carbon 002 plane spacing of the carbonaceous phase is to 0.3354 nm of ideal graphite.

[0088] The carbonaceous phase of the present negative electrode active material has an amorphous structure, and the interplanar spacing of carbon 002 planes determined by XRD measurement is 0.34 nm to 0.38 nm.

[0089] By setting the interplanar spacing of the carbon 002 planes of the carbonaceous phase to 0.34 nm to 0.38 nm, the electron conductivity of the negative electrode active material becomes good, and the isolation of Si nanoparticles accompanying volume expansion during charging can be suppressed, resulting in reduced capacity loss of Si nanoparticles.

[0090] In addition, the carbonaceous phase can also serve as a coating material for the negative electrode active material particles, thereby improving the electron conductivity between the negative electrode active material particles and suppressing the isolation of the negative electrode active material particles caused by swelling during charging, thereby improving the capacity retention rate when the secondary battery is manufactured.

[0091] From the viewpoint of coulomb efficiency, the interplanar spacing of carbon 002 planes determined by XRD measurement is preferably 0.345 nm to 0.375 nm, more preferably 0.350 nm to 0.370 nm.

[0092] The presence state of the aforementioned carbonaceous phase can be identified using a thermogravimetric differential thermal analyzer (TG-DTA). The carbonaceous phase is easily thermally decomposed in the atmosphere, and the amount of carbon present can be obtained by the thermal weight reduction measured in the presence of air. That is, the carbon amount of the carbonaceous phase can be quantified by using TG-DTA. In addition, by the thermal weight reduction behavior from the aforementioned measurement, it is also possible to easily grasp the changes in thermal decomposition temperature behavior such as the decomposition reaction start temperature, the decomposition reaction end temperature, the number of thermal decomposition reaction species, and the temperature of the maximum weight reduction of each thermal decomposition reaction species. The value of the temperature of these behaviors can be used to judge the state of carbon.

[0093] When the carbon in the carbonaceous phase is amorphous carbon, the carbonaceous phase has properties similar to those of amorphous carbon, and therefore is thermally decomposed in the atmosphere to a temperature range of about 550° C. to 900° C. As a result, a rapid weight loss occurs. The maximum temperature of the measurement conditions of TG-DTA is not particularly limited, but in order to completely terminate the thermal decomposition reaction of carbon, it is preferred to perform TG-DTA measurement in the atmosphere at about 25° C. to about 1000° C. or higher.

[0094] From the viewpoint of the formation of the structure of the negative electrode active material, the negative electrode active material preferably has a mass analysis reduction rate of 10% to 70% at 100 to 800° C. as determined by TG analysis under dry air flow.

[0095] As described above, the mass analysis reduction rate can be determined by performing TG-DTA measurement at 100° C. to 800° C. under the condition of dry air circulation.

[0096] The mass analysis reduction rate of the negative electrode active material at 100 to 800° C. obtained by TG analysis under dry air circulation is more preferably 15% to 65%, and further preferably 20% to 60%.

[0097] The weight increase start temperature of the negative electrode active material obtained based on TG analysis under dry air circulation is above 550°C, which means that a large amount of carbonaceous layer oxidized at low temperature exists. As a result, it is preferred from the perspective of suppressing the electrochemical side reactions on the surface of the active material by delaying the reaction between Si nanoparticles and oxygen and suppressing the reduction of capacity loss in the initial stage of the secondary battery.

[0098] From the viewpoint of suppressing the initial capacity loss and the initial coulombic efficiency, the weight increase start temperature is more preferably 575° C. or higher, and further preferably 600° C. or higher.

[0099] From the viewpoint of capacitance per unit weight, the negative electrode active material preferably contains 0.1 to 80 parts by mass of silicon-based materials relative to 100 parts by mass of the negative electrode active material. Silicon-based materials include silicon, carbided silicon oxide (silicon oxide carbide), etc. In the case where the negative electrode active material contains Si nanoparticles, silicon different from the nanoparticles is preferably used as the silicon material. As described later, in the case where the negative electrode active material has a carbon film, the mass of the negative electrode active material is the amount including the carbon film.

[0100] The specific surface area of ​​the negative electrode active material is preferably 0.01 m 2 / g to 20m 2 From the viewpoint of the amount of solvent absorbed during electrode preparation and the amount of binder used to maintain adhesion, the specific surface area of ​​the negative electrode active material is preferably 1 m 2 / g or more, more preferably 3m 2 / g or more. In addition, the specific surface area of ​​the negative electrode active material is preferably 18m 2 / g or less, more preferably 10m 2 / g or less.

[0101] In addition, the said specific surface area is the value calculated|required by the BET method similarly to the above.

[0102] The specific surface area of ​​the negative electrode active material can be calculated from the range where the adsorption heat C value is positive and linear based on the BET diagram, by determining the nitrogen adsorption amount at a relative pressure of 0.5 or less at liquid nitrogen temperature in the same manner as the aforementioned Si nanoparticles.

[0103] The average particle size of the negative electrode active material is preferably 0.5 μm to 10 μm, more preferably 2 μm to 8 μm. If the average particle size is too small, as the specific surface area increases significantly, when a secondary battery is made, the amount of SEI generated during charge and discharge increases, so that the reversible charge and discharge capacity per unit volume is sometimes reduced. If the average particle size is too large, it is possible to peel off from the collector when the electrode film is made. It should be noted that the average particle size is the volume average particle size as described above, which is the value of D50. The method for determining D50 is the same as described above.

[0104] In addition, the particle size range of the present electrode active material before classification is preferably 0.1 μm to 30 μm, and the particle size range after excluding fine powder particles is preferably 0.5 μm to 30 μm.

[0105] The negative electrode active material may be in any of the following shapes: granular, needle-like, or flake-like.

[0106] The present negative electrode active material has a carbon coating, and the porosity V defined by the following formula (1) is preferably 7% or more and 20% or less.

[0107]

[0108] In the above formula (1), V represents the porosity (%), and ρ represents the density inside the negative electrode active material (g / cm 3 ), ρ' represents the density of the entire negative electrode active material (g / cm 3 ), ρ" represents the density of the carbon film (g / cm 3 ), A represents the amount of carbon film (mass %).

[0109] The carbon film preferably covers at least a portion of the surface of the present negative electrode active material. The carbon film is preferably a film composed of low-crystalline carbon.

[0110] From the perspective of improving the chemical stability and thermal stability of the present negative electrode active material, the mass of the present negative electrode active material including the carbon film is set to 100 mass%, and the amount of the carbon film is preferably 0.1 mass% or more and 30 mass% or less, more preferably 1 mass% or more and 25 mass% or less, and further preferably 5 mass% or more and 20 mass% or less. In addition, from the perspective of improving the chemical stability and thermal stability of the present active material, the average thickness of the carbon film is preferably 10 nm or more and 300 nm or less.

[0111] From the perspective of improving the chemical stability and thermal stability of the present negative electrode active material, it is preferred that at least 1% of the surface of the present negative electrode active material has a carbon coating, and more preferably at least 10% has a carbon coating. The present negative electrode active material may have a carbon coating continuously or intermittently on its surface.

[0112] The carbon film is preferably formed on the surface of the negative electrode active material by chemical vapor deposition.

[0113] As mentioned above, it is believed that although Si nanoparticles have high capacity, they cause large volume changes due to the absorption and release of lithium ions in large quantities, resulting in poor cyclability. It is believed that the volume change cannot be fully suppressed by the carbon film alone. Therefore, a method of arranging gaps around Si nanoparticles and suppressing the destruction of the carbon film by buffering the volume expansion of the gaps is proposed. However, it is believed that if the gaps are inappropriate, the aforementioned buffering effect cannot fully function, the rupture of the active material causes an increase in surface area, and therefore the amount of SEI generated increases, and the initial coulomb efficiency decreases.

[0114] In addition, it is considered necessary to appropriately control the composition of the negative electrode active material together with the porosity.

[0115] It is considered that the state of the voids around Si nanoparticles is not necessarily appropriately reflected in the conventional definition of void ratio.

[0116] The inventors found that the porosity defined by the aforementioned formula (1) appropriately reflects the state of the voids around the Si nanoparticles. It was further found that by using a negative electrode active material whose porosity defined by the aforementioned formula (1) is in a specific range for a secondary battery, the increase in surface area and the generation of SEI caused by the rupture of the active material can be suppressed, and a secondary battery with improved initial coulomb efficiency can be obtained.

[0117] The above-mentioned densities ρ, ρ′ and ρ″ can be obtained by dry density measurement using a constant volume expansion method. ρ of the present negative electrode active material is usually about 2.0 to 2.4.

[0118] The density of the carbon film can be obtained by directly measuring the true density by peeling the carbon film from the present negative electrode active material, or by calculation, etc. For example, a curve of the content (mass %) of the carbon film and the density of the present negative electrode active material can be prepared at several points, and the point where the content of the carbon film becomes 100 mass % can be extrapolated by linear approximation to calculate the density of only the carbon film.

[0119] Alternatively, the silicon component may be dissolved from the present negative electrode active material and the true density of the insoluble portion may be directly measured.

[0120] In the above formula (1), A is the amount of the carbon coating, and is mass % when the mass of the negative electrode active material including the carbon coating is taken as 100 mass % as described above. The amount of the carbon coating can be determined by TG-DTA, elemental analysis, or the like.

[0121] Conventionally, the porosity is the ratio of voids in the entire particle, including pores and internal voids in the particle. The porosity (%) is generally defined by the following formula.

[0122] Void ratio (%) = (1-apparent density / true density) × 100

[0123] In the above formula, the apparent density is the density including the internal voids, and the porosity defined by the above formula is the voids other than the internal voids of the particles. As described above, in order to suppress the destruction of the active material particles having a carbon film, the gap between the carbon film and its interior is important, and the porosity of this part needs to be evaluated. Regarding the definition of porosity, various definitions have been proposed, including the porosity defined in the above-mentioned Patent Document 2, but the correlation between the porosity defined in the past and the density may be insufficient.

[0124] There is also a method of observing the particle cross section with an electron microscope or the like, visually confirming the voids and calculating the void ratio. However, this method is highly dependent on the particle cross-sectional area, and it is difficult to accurately determine the gap between the carbon film and its interior.

[0125] On the other hand, the definition of porosity based on the above formula (1) is different from the above-mentioned conventional method. In the negative electrode active material having a carbon coating, by introducing the amount and density of the carbon coating into the formula (1), the porosity of the gaps between the carbon coating and the interior thereof can be evaluated more accurately.

[0126] From the viewpoint of suppressing the influence of expansion caused by the insertion of lithium ions, the porosity V is preferably 9% or more, more preferably 11% or more. From the viewpoint of increasing the energy density of the obtained secondary battery, the porosity V is preferably 18% or less, more preferably 17% or less.

[0127] The carbon film is preferably formed on the surface of the negative electrode active material by chemical vapor deposition. To make the negative electrode active material within the above range of true density and porosity V, for example, the gas flow rate, treatment time, and treatment temperature during the carbon film treatment are controlled.

[0128] When the porosity V of the present negative electrode active material defined by the above formula (1) is 7% or more and 20% or less, the true density of the present negative electrode active material is preferably 1.6 g / cm 3 Above and 2.0g / cm 3 From the viewpoint of increasing the energy density of the obtained secondary battery, the true density is more preferably 1.65 g / cm 3 Above, particularly preferably 1.70 g / cm 3 above.

[0129] In addition, from the perspective of the relationship with the porosity V, the true density of the present negative electrode active material is more preferably 1.95 g / cm 3 Below, particularly preferably 1.90 g / cm 3 the following.

[0130] The above-mentioned true density is a value measured using a true density measuring device. It can be obtained by pressurizing the sample chamber containing the sample with helium, opening the valve, and calculating the volume of the sample from the pressure change caused by diffusing the gas into the expansion chamber, and then dividing the volume of the sample by the mass of the sample.

[0131] The present negative electrode active material may further contain a silicate compound in addition to the above-mentioned carbon coating.

[0132] The silicate compound is preferably a silicate compound of at least one metal selected from the group consisting of Li, K, Na, Ca, Mg, and Al.

[0133] The silicate compound is generally an anion-containing compound having a structure with one or more silicon atoms as the center and surrounded by electronegative ligands, and is preferably a silicate compound that is a salt of at least one metal selected from the group consisting of Li, K, Na, Ca, Mg and Al and the aforementioned anion-containing compound.

[0134] As the aforementioned compound containing anions, orthosilicate ions (SiO4 4- ), metasilicate ion (SiO3 2- ), pyrosilicate ion (Si2O7 6- ), cyclic silicate ions (Si3O9 6- or Si6O 18 12- ) and other silicate ions. The silicate compound is preferably a silicate compound that is a salt of a metasilicate ion and at least one metal selected from the group consisting of Li, K, Na, Ca, Mg and Al. Among the above metals, Li or Mg is more preferred.

[0135] When the silicate compound has at least one metal selected from the group consisting of Li, K, Na, Ca, Mg and Al, it may have two or more of these metals. When it has two or more metals, one silicate ion may have multiple metals or a mixture of silicate compounds having different metals. In addition, as long as the silicate compound has at least one metal selected from the group consisting of Li, K, Na, Ca, Mg and Al, it may also have other metals.

[0136] The silicate compound is preferably a lithium silicate compound or a magnesium silicate compound, more preferably lithium metasilicate (Li2SiO3) or magnesium metasilicate (MgSiO3), and particularly preferably magnesium metasilicate (MgSiO3).

[0137] When the silicate compound is in a crystalline state, it can be detected by powder X-ray diffraction measurement (XRD), and when it is amorphous, it can be detected by solid 29 This was confirmed by Si-NMR measurement.

[0138] Since the negative electrode active material has the aforementioned carbonaceous phase, in the Raman spectrum of the carbonaceous phase, the carbon structure has a G band of 1590 cm-1, which belongs to the graphite long period carbon lattice structure. -1 The scattering peaks near the graphite and the D band at 1330 cm-1, which is attributed to the disordered or defective short-period carbon lattice structure of graphite, are also present. -1 The scattering peaks near the D band have a scattering peak intensity ratio I (G band / D band) preferably in the range of 0.7 to 2. The scattering peak intensity ratio I is more preferably in the range of 0.7 to 1.8.

[0139] When the negative electrode active material has the low-crystalline carbon coating layer, the scattering peak intensity ratio I (G band / D band) of the Raman spectrum of the negative electrode active material is preferably in the range of 0.9 to 1.1.

[0140] The present negative electrode active material may contain other components as necessary in addition to the aforementioned silicon-based material, carbon coating, and silicate compound.

[0141] The present negative electrode active material can be produced, for example, by a method including the following steps 1 to 3. It should be noted that the following steps illustrate the method when Si nanoparticles are included, but are not limited to this method. When the present negative electrode active material includes acidic silicon, the Si nanoparticles can be changed to silicon oxide particles in the following step 1. When the present negative electrode active material includes Si nanoparticles and silicon oxide particles, Si nanoparticles and silicon oxide particles can be used in the following step 1. As described above, silicon oxide particles can be produced by cooling and precipitating silicon monoxide gas generated by heating a mixture of silicon dioxide and metallic silicon. In addition, commercially available silicon oxide can also be used. Step 1: A slurry of Si nanoparticles crushed by a wet method is mixed with a carbonaceous phase source, stirred, and dried to obtain a precursor. Step 2: The precursor obtained in the above step 1 is calcined in an inert atmosphere at a temperature range of 1000°C to 1180°C to obtain a calcined product. Step 3: The calcined product obtained in the above step 2 is crushed to obtain the present negative electrode active material.

[0142] Hereinafter, each step will be described.

[0143] <Process 1>

[0144] (Si(0) slurry)

[0145] The preparation of the Si (0 valence) slurry pulverized by the wet method used in step 1 can be carried out while pulverizing the silicon particles with a wet powder pulverizing device using an organic solvent. In order to promote the pulverization of the silicon particles in the organic solvent, a dispersant can also be used. As a wet pulverizing device, there is no particular limitation, and a roller mill, a high-speed rotating pulverizer, a container-driven mill, a bead mill, etc. can be cited.

[0146] In the wet pulverization, it is preferred to pulverize the silicon particles until they become Si nanoparticles.

[0147] The organic solvent used in the wet method is an organic solvent that does not chemically react with silicon. Examples include ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and diisobutyl ketone; alcohols such as ethanol, methanol, n-propanol, and isopropanol; and aromatics such as benzene, toluene, and xylene.

[0148] The types of the above-mentioned dispersants can use aqueous and non-aqueous dispersants. In order to suppress excessive oxidation of the surface of the silicon particles, it is preferred to use a non-aqueous dispersant. The types of non-aqueous dispersants can be exemplified by: polymer types such as polyether, polyalkylene polyamine, and polycarboxylic acid partial alkyl ester; low molecular types such as polyol ester, alkyl polyamine; inorganic types such as polyphosphate. The concentration of silicon in the Si (0-valent) slurry is not particularly limited. In the case of containing the aforementioned solvent and the dispersant as needed, the total amount of the dispersant and the Si particles is set to 100 mass%, and the amount of Si particles is preferably in the range of 5 mass% to 40 mass%, and more preferably 10 mass% to 30 mass%.

[0149] (Carbonaceous phase source)

[0150] As the carbonaceous phase source used in the above step 1, it is preferable to use a synthetic resin or a natural chemical raw material which is carbonized by high-temperature calcination in an inert atmosphere and has an aromatic functional group.

[0151] As synthetic resins, thermoplastic resins such as polyvinyl alcohol and polyacrylic acid, and thermosetting resins such as phenolic resins and furan resins can be cited. As natural chemical raw materials, coke and heavy oil can be cited, and in particular, as tar pitches, coal tar, tar light oil, tar medium oil, tar heavy oil, naphthalene oil, anthracene oil, coal tar pitch, asphalt oil, mesophase pitch, oxygen-crosslinked petroleum pitch, heavy oil, etc. can be cited.

[0152] (Precursor)

[0153] The carbonaceous phase source and the Si slurry are uniformly mixed, stirred, desolvated and dried to obtain a precursor of the present negative electrode active material (hereinafter also referred to as "precursor"). The mixing is performed using a device having a dispersing and mixing function. For example, a stirrer, an ultrasonic mixer, a premixing disperser, etc. can be cited. In the desolvation and drying operation for the purpose of distilling off the organic solvent, a dryer, a reduced pressure dryer, a spray dryer, etc. can be used.

[0154] Precursor preferably contains 3 mass % to 97 mass % of Si nanoparticles as Si (0 valence), 3 mass % to 97 mass % of the solid component of the carbonaceous phase source, more preferably contains 20 mass % to 80 mass % of the solid component content of silicon particles, 20 mass % to 80 mass % of the solid component of the carbon source resin.By the precursor of the negative electrode active material is subjected to the heat treatment described later, so that the quality is reduced, the ratio of the nano silicon in the negative electrode active material is likely to change, so the content of the Si nanoparticles in the precursor is appropriately set based on the content of the Si nanoparticles in the negative electrode active material as the target.

[0155] <Process 2>

[0156] Step 2 is a process in which the precursor obtained in the above step 1 is fired in an inert atmosphere at a temperature range of 1000°C to 1180°C, thereby completely decomposing the thermally decomposable organic components, and the other main components are made into a fired product suitable for the present negative electrode active material by precise control of the firing conditions. Specifically, the carbonaceous phase source of the raw material is converted into free carbon by the energy of high-temperature treatment. That is, a matrix of a fired product containing a carbonaceous phase source is obtained by firing. The fired product mentioned here refers to organic compounds such as carbonaceous phase sources that are decomposed and converted at high temperatures, thereby changing part or all of their composition and structure.

[0157] Regarding the burned product of the carbonaceous phase source, the carbonaceous phase source may be entirely converted into carbon, or a portion thereof may be converted into carbon while the remaining portion maintains the structure of the carbonaceous phase source.

[0158] In step 2, the precursor obtained in step 1 is fired in an inert atmosphere according to a firing procedure specified by a heating rate, a holding time at a certain temperature, etc. The maximum reaching temperature is the highest temperature set, and has a strong influence on the structure and performance of the present negative electrode active material as a fired product. In the present invention, by setting the maximum reaching temperature to 1000°C to 1180°C, the fine structure of the present negative electrode active material can be precisely controlled, and the oxidation of silicon particles during over-high temperature firing can be avoided, thereby obtaining more excellent charge and discharge characteristics.

[0159] The firing method is not particularly limited, and a reaction device with a heating function can be used in an inert atmosphere, and the process can be carried out by a continuous method or a batch method. Regarding the firing device, a fluidized bed reactor, a rotary kiln, a vertical moving bed reactor, a tunnel furnace, an intermittent furnace, a rotary kiln, etc. can be appropriately selected according to its purpose.

[0160] <Process 3>

[0161] Step 3 is a step of pulverizing the calcined product obtained in the above-mentioned step 2, and classifying it as needed to obtain the present negative electrode active material. In addition, step 3 is a step of making a carbon film on the surface of the negative electrode active material by chemical vapor deposition as needed. The pulverization can be carried out in one stage to the target particle size, or it can be carried out in multiple stages. For example, when the calcined product is a block or agglomerated particles of more than 10 mm and an active material of 10 μm is made, it is coarsely pulverized with a jaw crusher, a roller crusher, etc., and after being made into particles of about 1 mm, it is made into 100 μm with a GROWMILL, a ball mill, etc., and pulverized to 10 μm with a bead mill, a jet mill, etc. The particles produced by pulverization sometimes contain coarse particles. In order to remove them, classification is performed in addition to removing fine powder and adjusting the particle size distribution. The classifier used uses a wind classifier, a wet classifier, etc. according to the purpose. When removing coarse particles, the classification method by sieve can reliably achieve the purpose, so it is preferred. Note that, when the precursor mixture is controlled to have a shape close to the target particle size by spray drying or the like before firing, and the main firing is performed in this shape, the pulverization step can of course be omitted.

[0162] In the aforementioned manufacturing process, by controlling the gas flow rate during the carbon coating treatment, optimizing the treatment time, and the treatment temperature conditions, the true density of the present negative electrode active material and the porosity defined by the aforementioned formula (1) can be made within the aforementioned range. For example, by increasing the gas flow rate and the treatment time, the amount of coated carbon can be increased, and the porosity defined by the aforementioned formula (1) can be adjusted. In addition, by increasing the treatment temperature, the true density can be increased.

[0163] In addition, in the aforementioned manufacturing process, by controlling the firing temperature, the interplanar spacing and specific surface area of ​​the carbonaceous phase of the present negative electrode active material determined by XRD measurement can be within the aforementioned range. For example, if the firing temperature is increased, the carbonization reaction proceeds and the interplanar spacing of the carbon 002 plane becomes narrower.

[0164] In the case where the present negative electrode active material has a silicate compound of at least one metal selected from the group consisting of Li, K, Na, Ca, Mg and Al, a salt of at least one metal selected from the group consisting of Li, K, Na, Ca, Mg and Al is added to a suspension obtained by mixing a slurry of Si nanoparticles with a carbonaceous phase source, and then the present active material having the aforementioned silicate compound is obtained by the same operation as above.

[0165] Examples of the salt of at least one metal selected from the group consisting of Li, K, Na, Ca, Mg and Al include halides such as fluorides, chlorides and bromides, hydroxides and carbonates of these metals.

[0166] The metal salt may be a salt of two or more metals, may contain a plurality of metals in one salt, or may be a mixture of salts containing different metals.

[0167] When the metal salt is added to the suspension, the amount of the metal salt added is preferably 0.01 to 0.4 in terms of molar ratio relative to the number of moles of the Si nanoparticles.

[0168] When the salt of the aforementioned metal is soluble in an organic solvent, the salt of the aforementioned metal is dissolved in an organic solvent and added to a suspension of a carbonaceous phase source for mixing, or when the present active material particles include Si nanoparticles, it is added to a suspension of Si nanoparticles for mixing. When the salt of the aforementioned metal is insoluble in an organic solvent, the particles of the metal salt are dispersed in an organic solvent and then added to a suspension of a carbonaceous phase source for mixing, or when the present active material particles include Si nanoparticles, it is added to a suspension of Si nanoparticles for mixing. From the viewpoint of improving the dispersion effect, the salt of the aforementioned metal is preferably a nanoparticle with an average particle size of less than 100 nm. The aforementioned organic solvent can preferably use alcohols, ketones, etc., and aromatic hydrocarbon solvents such as toluene, xylene, naphthalene, and methylnaphthalene can also be used.

[0169] When the present negative electrode active material has the aforementioned carbon film, the present negative electrode active material having the carbon film can be obtained by coating at least a portion of the surface of the calcined product obtained by the aforementioned method with the carbon film. The carbon film is preferably an amorphous carbon film obtained in a chemical vapor deposition device in a temperature range of 700° C. to 1000° C. in a pyrolytic carbon source gas and an inactive carrier gas flow.

[0170] Examples of the thermally decomposable carbon source gas include acetylene, ethylene, acetone, alcohol, propane, methane, and ethane.

[0171] Examples of the inert gas include nitrogen, helium, and argon, and nitrogen is usually used.

[0172] When the present negative electrode active material contains a silicon-based material, in the above-mentioned step 1, a silicon material source as a target silicon-based material may be added together with a carbonaceous phase source.

[0173] Examples of the silicon material source include polyalkoxysilane, polysilsesquioxane, and polysiloxane-containing acrylic resin.

[0174] The present negative electrode active material has excellent initial coulombic efficiency, and thus a secondary battery using a battery negative electrode including the present negative electrode active material exhibits good charge and discharge characteristics.

[0175] Specifically, a slurry containing the present negative electrode active material, an organic binder, and other conductive additives as needed can be formed into a thin film on a current collector copper foil and used as a negative electrode. In addition, a carbon material can be added to the slurry to make a negative electrode.

[0176] Examples of the carbon material include natural graphite, artificial graphite, and amorphous carbon such as hard carbon and soft carbon.

[0177] The present negative electrode active material and the binder as an organic binding material can be mixed with a solvent using a dispersing device such as a stirrer, a ball mill, a super sand mill, a pressure kneading machine, etc. to prepare a negative electrode material slurry, which is applied to the collector to form a negative electrode layer. In addition, it can also be obtained by molding the paste-like negative electrode material slurry into a sheet, granular, etc. shape, and integrating it with the collector. The negative electrode obtained by the above-mentioned becomes a negative electrode for a secondary battery with excellent initial coulomb efficiency because it contains the present negative electrode active material. The above-mentioned negative electrode can be obtained, for example, as follows: the present negative electrode active material and the binder as an organic binding material are mixed with a solvent using a dispersing device such as a stirrer, a ball mill, a super sand mill, a pressure kneading machine, etc., to prepare a negative electrode material slurry, which is applied to the collector to form a negative electrode layer. In addition, it can also be obtained by molding the paste-like negative electrode material slurry into a sheet, granular, etc. shape, and integrating it with the collector.

[0178] Examples of the aforementioned organic binder include: styrene-butadiene rubber copolymer (SBR); unsaturated carboxylic acid copolymers such as (meth)acrylic acid copolymers composed of ethylenically unsaturated carboxylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, (meth)acrylonitrile and hydroxyethyl (meth)acrylate, and ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, fumaric acid and maleic acid; and polymer compounds such as polyvinylidene fluoride, polyethylene oxide, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polyimide, polyamide-imide and carboxymethyl cellulose (CMC).

[0179] These organic binders are dispersed or dissolved in water according to their physical properties, and organic binders dissolved in organic solvents such as N-methyl-2-pyrrolidone (NMP). The organic binder content in the negative electrode layer of the negative electrode of the lithium ion secondary battery is preferably 1% to 30% by mass, more preferably 2% to 20% by mass, and further preferably 3% to 15% by mass.

[0180] When the content of the organic binder is 1% by mass or more, the adhesion is better and the destruction of the negative electrode structure due to expansion and contraction during charge and discharge can be further suppressed. On the other hand, when the content is 30% by mass or less, the increase in electrode resistance can be further suppressed.

[0181] Within this range, the negative electrode active material of the present invention has high chemical stability and can be used with an aqueous binder, and is easy to handle in terms of practical application.

[0182] In addition, a conductive aid may be mixed into the negative electrode material slurry as needed. As the conductive aid, for example, carbon black, graphite, acetylene black, or oxides and nitrides showing conductivity may be cited. The amount of the conductive aid used is about 1% to 15% by mass relative to the negative electrode active material of the present invention.

[0183] In addition, regarding the material and shape of the collector, for example, copper, nickel, titanium, stainless steel, etc. can be used as a strip collector made into a foil, perforated foil, mesh, etc. In addition, porous materials such as porous metal (foamed metal), carbon paper, etc. can also be used.

[0184] As a method for applying the negative electrode material slurry to the current collector, for example, metal mask printing, electrostatic coating, dip coating, spraying, roll coating, doctor blade, gravure coating, screen printing, etc. can be cited. After coating, it is preferably rolled using a flat press, a calendering roll, etc. as needed.

[0185] The negative electrode material slurry may be formed into a sheet or pellet form and integrated with the current collector by, for example, a roller, a press, or a combination thereof.

[0186] The negative electrode layer formed on the collector and the negative electrode layer integrated with the collector are preferably heat-treated according to the organic binder used. For example, when using water-based styrene-butadiene rubber copolymer (SBR) and the like, heat treatment is performed at 100 to 130°C, and when using an organic binder with polyimide or polyamide-imide as the main skeleton, heat treatment is preferably performed at 150 to 450°C.

[0187] By this heat treatment, the removal of solvent, the high strength brought by the solidification of binder can improve the adhesion between particles and between particles and collector. It should be noted that, in order to prevent the oxidation of the collector in the process, these heat treatments are preferably carried out under inactive atmospheres such as helium, argon, nitrogen, or vacuum atmosphere.

[0188] In addition, after the heat treatment, the negative electrode is preferably pressed (pressurized) in advance. In the negative electrode using the negative electrode active material of the present invention, the electrode density is preferably 1 g / cm 3 Up to 1.8g / cm 3 , more preferably 1.1 g / cm 3 Up to 1.7g / cm 3 , more preferably 1.2 g / cm 3Up to 1.6g / cm 3 Regarding electrode density, there is a tendency that the higher the electrode density, the better the adhesion and volume capacity density of the electrode. However, if the density is too high, the voids in the electrode are reduced, thereby weakening the effect of suppressing volume expansion of silicon and the like, and reducing the capacity retention rate. Therefore, the optimal range is selected.

[0189] The negative electrode containing the present negative electrode active material is suitable for use in a secondary battery due to its excellent initial coulombic efficiency. As a secondary battery having the negative electrode, a nonaqueous electrolyte secondary battery and a solid electrolyte secondary battery are preferred, and the negative electrode particularly exhibits excellent performance when used as a negative electrode of a nonaqueous electrolyte secondary battery.

[0190] When used in a wet electrolyte secondary battery, for example, the secondary battery containing the negative electrode active material of the present invention can be constructed by arranging a positive electrode and a negative electrode containing the negative electrode active material of the present invention facing each other via a separator and injecting an electrolyte solution.

[0191] The positive electrode can be obtained by forming a positive electrode layer on the surface of a current collector in the same manner as the negative electrode. The current collector in this case can be a strip-shaped current collector made of a metal or alloy such as aluminum, titanium, stainless steel, etc. in the form of foil, perforated foil, mesh, etc.

[0192] There is no particular restriction on the positive electrode material used in the positive electrode layer. In a non-aqueous electrolyte secondary battery, when a lithium ion secondary battery is made, for example, a metal compound, metal oxide, metal sulfide or conductive polymer material that can be doped or embedded with lithium ions can be used. For example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), and their composite oxides (LiCoxNiyMnzO2, x+y+z=1), lithium manganese spinel (LiMn2O4), lithium vanadium compounds, V2O5, V6O 13 , VO2, MnO2, TiO2, MoV2O8, TiS2, V2S5, VS2, MoS2, MoS3, Cr3O8, Cr2O5, olivine-type LiMPO4 (M: Co, Ni, Mn, Fe), polyacetylene, polyaniline, polypyrrole, polythiophene, polybenzone and other conductive polymers, porous carbon, etc.

[0193] As the separator, for example, nonwoven fabrics, cloths, microporous membranes or combinations thereof with polyolefins such as polyethylene and polypropylene as the main components can be used. It should be noted that, in the case of a structure in which the positive electrode of the nonaqueous electrolyte secondary battery to be manufactured is not in direct contact with the negative electrode, a separator is not required.

[0194] As the electrolyte, for example, a so-called organic electrolyte can be used, which is prepared by dissolving a lithium salt such as LiClO4, LiPF6, LiAsF6, LiBF4, LiSO3CF3 in a non-aqueous solvent such as ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, fluoroethylene carbonate, cyclopentanone, sulfolane, 3-methylsulfolane, 2,4-dimethylsulfolane, 3-methyl-1,3-oxazolidin-2-one, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, butyl methyl carbonate, ethyl propyl carbonate, butyl ethyl carbonate, dipropyl carbonate, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, methyl acetate, ethyl acetate, or a monomer or a mixture of two or more components.

[0195] The structure of the secondary battery containing the present negative electrode active material is not particularly limited, and is usually made into the following structure: the positive electrode and the negative electrode and the separator set as needed are wound into a flat spiral shape to form a wound electrode plate group, or they are stacked in a flat plate shape to form a stacked electrode plate group, and these electrode plate groups are sealed in an outer package. It should be noted that the half-battery used in the embodiment of the present invention was evaluated in a simple manner in which the negative electrode adopts the present negative electrode active material as the main body and the electrode uses metallic lithium, in order to more clearly compare the cycle characteristics of the active material itself. A small amount of the present negative electrode active material is added to the mixture mainly composed of a graphite-based active material (capacity of about 340mAh / g), so that the negative electrode capacity is about 400 to 700mAh / g, which greatly exceeds the existing negative electrode capacity, and the cycle characteristics can be improved.

[0196] The secondary battery containing the negative electrode active material is not particularly limited, and can be used as a paper battery, a button battery, a coin battery, a stacked battery, a cylindrical battery, a square battery, etc. The aforementioned negative electrode active material can also be applied to all electrochemical devices with the charging and discharging mechanism of inserting and extracting lithium ions, such as hybrid capacitors, solid lithium secondary batteries, etc.

[0197] As described above, the negative electrode active material of the present invention provides a secondary battery having high initial efficiency and excellent balance of battery characteristics, which are one of the important properties of a secondary battery. Therefore, the present negative electrode active material can be suitably used in a secondary battery.

[0198] As mentioned above, although this negative electrode active material and the secondary battery which has this negative electrode active material were demonstrated, this invention is not limited to the structure of the said embodiment.

[0199] The present negative electrode active material and the secondary battery having the present negative electrode active material may add any other configuration to the configuration of the above-mentioned embodiment, or may replace it with any configuration that exhibits the same function.

[0200] Example

[0201] Hereinafter, the present invention will be described in detail with reference to Examples, but the present invention is not limited thereto.

[0202] It should be noted that the half-cell used in the embodiment of the present invention was simply evaluated using the present negative electrode active material for the negative electrode and metallic lithium for the counter electrode, in order to more clearly compare the cycle characteristics of the active material itself. By setting this configuration, by adding a small amount of the present negative electrode active material to a mixture mainly composed of a graphite-based active material with a capacity of about 340 mAh / g, it is possible to suppress the negative electrode capacity of about 400 to 700 mAh / g, which greatly exceeds the existing negative electrode capacity, while improving the cycle characteristics.

[0203] (Example 1)

[0204] The present negative electrode active material was prepared as follows.

[0205] Agglomerates of silicon (0 valent) are pulverized in a dispersant by a wet pulverization method using a bead mill to obtain a slurry of silicon nanoparticles.

[0206] The Si nanoparticle slurry was mixed with a phenolic resin so that the composition after firing was Si / C = 0.5 / 0.5 in mass ratio, and the precursor obtained by reduced pressure drying was fired at 1100° C. for 6 hours in a nitrogen atmosphere to obtain a black solid material containing Si and C.

[0207] The obtained black solid material was crushed with a planetary ball mill, and the obtained black powder was subjected to thermal CVD (chemical vapor deposition), thereby obtaining a negative electrode active material with a carbon film. At this time, the thermal CVD used a rotary kiln type reactor in a nitrogen atmosphere, and LPG (liquid propane gas) was used as a carbon source. The temperature in the furnace was set to 900°C, the pressure was set to 1 atm, and the CVD time was set to 360 minutes. The obtained negative electrode active material had an average particle size (D50) of 4.7 μm and a particle size of 13.2 μm. 2 The amount of carbon film of the obtained negative electrode active material was 25.7% according to TG-DTA, and the true density was 1.91 g / cm 3 , the void fraction calculated thereby is 7.3%.

[0208] Next, a half-cell was prepared using the negative electrode active material obtained above, and the charge-discharge characteristics were evaluated. According to the charge-discharge measurement results, the initial coulomb efficiency was 83.2%. The evaluation results are shown in Table 1.

[0209] (Example 2)

[0210] The negative electrode active material was obtained in the same manner as in Example 1 except that the thermal CVD time was changed to 120 minutes.

[0211] (Example 3)

[0212] The raw coke was crushed and classified in such a way that D50 became 7.9 μm, and as a carbonaceous phase source, the raw coke particles and silica particles were mixed and dry granulated. At this time, the amount of silica particles added when the sum of the volume of silica particles and raw coke particles was set to 100% was 53% by volume. The amount of silica particles added when the sum of the mass of silica particles and raw coke particles was set to 100% was 61% by mass. Then, the granulated particles were calcined at 1000° C. for 5 hours in a nitrogen atmosphere to perform a carbonization treatment.

[0213] The obtained black powder was subjected to thermal CVD (chemical vapor deposition) to obtain a negative electrode active material with a carbon coating. At this time, the thermal CVD used a rotary kiln type reactor, LPG (liquid propane gas) as the carbon source, the temperature in the furnace was set to 900°C, the pressure was set to 1 atm, and the CVD time was set to 260 minutes. The amount of carbon coating of the obtained negative electrode active material was 12.4% according to TG-DTA, and the true density was 1.78 g / cm 3 , the void fraction calculated thereby is 10.9%.

[0214] Next, a half-cell was prepared using the negative electrode active material obtained above, and the charge-discharge characteristics were evaluated. According to the charge-discharge measurement results, the initial coulomb efficiency was 71.0%. The evaluation results are shown in Table 1.

[0215] (Example 4 to Example 6)

[0216] Negative electrode active materials were obtained in the same manner as in Example 3 except that the thermal CVD time in Example 3 was changed to 200 minutes in Example 4, to 300 minutes in Example 5, and to 360 minutes in Example 6. The evaluation results of half cells using the obtained negative electrode active materials are shown in Table 1.

[0217] (Example 7)

[0218] A negative electrode active material was obtained in the same manner as in Example 3 except that the calcination temperature was changed to 1200° C. and the thermal CVD time was changed to 180 minutes. Table 1 shows the evaluation results of half cells using the obtained negative electrode active material.

[0219] (Example 8 to Example 10)

[0220] A negative electrode active material was obtained in the same manner as in Example 7 except that the thermal CVD time in Example 7 was changed to 240 minutes in Example 8, to 320 minutes in Example 9, and to 400 minutes in Example 10. The evaluation results of the half-cells using the obtained negative electrode active materials are shown in Table 1.

[0221] (Example 11)

[0222] The negative electrode active material was obtained in the same manner as in Example 1 except that the thermal CVD in Example 1 was not carried out. The evaluation results are shown in Table 1.

[0223] (Example 12)

[0224] The negative electrode active material was obtained in the same manner as in Example 3 except that the thermal CVD of Example 3 was not carried out. The evaluation results are shown in Table 1.

[0225] (Example 13)

[0226] A negative electrode active material was obtained in the same manner as in Example 7 except that the thermal CVD of Example 7 was not performed. Table 1 shows the evaluation results of half cells using the obtained negative electrode active material.

[0227] (Example 14)

[0228] A negative electrode active material was obtained in the same manner as in Example 3 except that the reaction time of the thermal CVD in Example 3 was changed to 80 minutes. Table 1 shows the evaluation results of the half cell using the obtained negative electrode active material.

[0229] (Example 15)

[0230] A negative electrode active material was obtained in the same manner as in Example 7 except that the reaction time of the thermal CVD in Example 7 was changed to 90 minutes. Table 1 shows the evaluation results of the half cell using the obtained negative electrode active material.

[0231] (Comparative Example 1)

[0232] A negative electrode active material with a carbon coating is obtained by subjecting SiO particles with an average particle size of 5 μm to thermal CVD (chemical vapor deposition). At this time, a rotary kiln type reactor is used for thermal CVD, LPG (liquid propane gas) is used as the carbon source, the temperature in the furnace is set to 900°C, the pressure is set to 1 atm, and the CVD time is set to 180 minutes. Since the SiO particles in the obtained negative electrode active material are not embedded in the carbonaceous phase, no diffraction peak attributable to the d002 plane is obtained in the XRD measurement. The amount of carbon coating of the obtained negative electrode active material is 6.1% according to TG-DTA, and the true density is 2.23 g / cm 3The porosity calculated from this was 1.3%. Table 1 shows the evaluation results of the half-cell using the obtained negative electrode active material.

[0233] (Comparative Example 2)

[0234] The negative electrode active material was obtained in the same manner as in Comparative Example 1 except that the thermal CVD time of Comparative Example 1 was changed to 150 minutes. Since the SiO particles in the obtained negative electrode active material were not embedded in the carbonaceous phase, no diffraction peak attributable to the d002 plane was obtained in the XRD measurement. The amount of the carbon film was 5.0% according to TG-DTA, and the true density was 2.24 g / cm 3 The porosity calculated from this was 1.2%. Table 1 shows the evaluation results of the half-cell using the obtained negative electrode active material.

[0235] (Comparative Example 3)

[0236] The SiO particles of Comparative Example 1 were evaluated and the true density was 2.32 g / cm 3 Since the SiO particles in the obtained negative electrode active material were not embedded in the carbonaceous phase, no diffraction peak attributable to the d002 plane was obtained in the XRD measurement. Table 1 shows the evaluation results of the half-cell using the obtained negative electrode active material.

[0237] [Table 1]

[0238]

[0239] BET (specific surface area): Measured by nitrogen adsorption using a specific surface area measuring device (BELSORP-mini, manufactured by BELJAPAN). The amount of nitrogen adsorbed at a relative pressure of 0.5 or less at liquid nitrogen temperature was determined at multiple points, and the specific surface area was calculated from the BET diagram within the range where the adsorption heat C value was positive and linearity was high.

[0240] Determination of the interplanar spacing of the d002 plane: Using Ultima IV manufactured by Rigaku Corporation and CuKα X-ray source, 2θ is measured with a goniometer in the range of 1 to 70° as a reflection method. The interplanar spacing of the carbon 002 plane of the negative electrode active material of the present invention can be evaluated as follows. That is, the negative electrode active material containing the carbonaceous phase is filled in the sample holder, and CuKα rays are used as the ray source to obtain an X-ray diffraction pattern. The peak position of the X-ray diffraction pattern is calculated by the 2θ value, and the wavelength of the CuKα ray is set to 0.15418nm, and the carbon phase 002 interplanar spacing is calculated by the Bragg formula described below.

[0241] d002=λ / 2·sinθ

[0242] Thermogravimetric increase temperature: Using a differential thermogravimetric analyzer (Thermo PLUSEVO2) manufactured by Rigaku, 10 mg of negative electrode active material was placed in an alumina pan, and the temperature was raised to 1000°C at 200 ml / min and a heating rate of 10°C / min under a dry air flow. The thermogravimetric change during the temperature increase was measured, and the weight loss was calculated as negative and the weight increase was calculated as positive. Then, the temperature at which the weight loss turned into the weight increase was taken as the weight increase start temperature.

[0243] Thermogravimetric reduction rate: Using a differential thermogravimetric analyzer (Thermo PLUSEVO2) manufactured by Rigaku, 10 mg of negative electrode active material was placed in an alumina pan, and the temperature was raised to 1000°C at 200 ml / min and a heating rate of 10°C / min under a dry air flow, and the thermogravimetric change during the heating was measured. The weight percentage at the temperature at which the weight begins to decrease at a temperature (above 100°C) where the attached water is considered to evaporate was used as the basis, and the weight percentage with the smallest weight reduction rate was subtracted for calculation.

[0244] True density: The true density was measured using a true density measuring device (Ultrapyc 5000micro, manufactured by Anton Paar) with helium as the gas used at a temperature of 25° C. and a measurement pressure of 115 kPa.

[0245] Porosity: Calculated based on the above formula (1). Note that ρ" was calculated to be 1.6 (g / cm 3 ).

[0246] Evaluation of battery characteristics: Battery characteristics were measured using a secondary battery charge and discharge tester (manufactured by Hokuto Denko Co., Ltd.), and the initial coulombic efficiency was determined as follows at room temperature 25° C. and a cutoff voltage range of 0.005 to 1.5 V.

[0247] Initial Coulombic efficiency of negative electrode active material: Electrochemical evaluation was performed and calculated as follows.

[0248] A half-cell for evaluation using the electrode active material was assembled as follows, and the charge and discharge characteristics were measured.

[0249] First, the negative electrode active material (8 parts), 1 part of acetylene black as a conductive aid and 1 part of an organic binder were mixed and stirred for 10 minutes using a rotation-revolution defoamer to prepare a negative electrode material slurry. It should be noted that the organic binder is a mixture of 0.75 parts of styrene-butadiene copolymer rubber (commercially available SBR), 0.25 parts of carboxymethyl cellulose (CMC) and 10 parts of distilled water.

[0250] After applying it to a copper foil with a thickness of 20 μm using an applicator, it was dried under reduced pressure at 110°C to obtain an electrode film with a thickness of about 40 μm. It was punched into a circular electrode with a diameter of 14 mm and pressed at a pressure of 20 MPa. In a glove box with an oxygen concentration of less than 10 ppm and a moisture content of less than -40°C at a dew point, the Li foil was used as a counter electrode, and the electrodes of the present invention were placed opposite to each other through a 25 μm polypropylene diaphragm, and the electrolyte (Kishida Chemical, 1 mol / L LiPF6, diethyl carbonate: ethylene carbonate = 1:1 (volume ratio)) was adsorbed to make a half-cell (CR2032 type) for evaluation.

[0251] The battery characteristics were measured using a secondary battery charge and discharge tester (manufactured by Hokuto Denko Co., Ltd.), and the charge and discharge characteristics were evaluated under the following conditions: room temperature 25°C, cut-off voltage range 0.005 to 1.5V, charge and discharge rate 0.1C for 1 to 3 cycles, 0.2C after 4 cycles, constant current-constant voltage charging / constant current discharging. When switching between each charge and discharge, the battery was left in an open circuit for 30 minutes. The initial coulomb efficiency was determined as follows.

[0252] Initial Coulombic efficiency (%) = initial discharge capacity (mAh / g) / initial charge capacity (mAh / g)

[0253] From the above results, it is understood that the secondary battery using the present negative electrode active material is excellent in initial coulombic efficiency.

Claims

1. A negative electrode active material comprising at least one of Si nanoparticles or silicon oxide particles and a carbonaceous phase, wherein the carbonaceous phase embeds at least one of the Si nanoparticles or the silicon oxide particles, and the interplanar spacing of the carbon 002 planes in the carbonaceous phase determined by XRD measurement is 0.34 nm to 0.38 nm.

2. The negative electrode active material according to claim 1, wherein The thermal weight reduction rate at 100° C. to 800° C. obtained by TG analysis under dry air circulation is 10 to 70% by weight.

3. The negative electrode active material according to claim 1 or 2, wherein The weight increase start temperature obtained by TG analysis under dry air flow was 550° C. or higher. 4 . The negative electrode active material according to claim 1 , comprising 0.1 wt % to 80 wt % of a silicon-based material.

5. The negative electrode active material according to claim 1 or 2, wherein The specific surface area is 0.01m 2 / g to 20m 2 / g.

6. The negative electrode active material according to claim 1 or 2, wherein The average particle size is 0.5 μm to 10 μm.

7. The negative electrode active material according to claim 1 or 2, which has a carbon coating, a porosity defined by the following formula (1) of 7% or more and 20% or less, and a true density of 1.6 g / cm 3 Above and 2.0g / cm 3 the following, In formula (1), V represents the porosity, the unit is %, and ρ represents the density inside the negative electrode active material, the unit is g / cm 3 , ρ' represents the density of the entire negative electrode active material, in g / cm 3 , ρ" represents the density of the carbon film, the unit is g / cm 3 , A represents the amount of the carbon film, and the unit is mass %. 8 . A secondary battery comprising the negative electrode active material according to claim 1 .

Citation Information

Patent Citations

  • Negative electrode active material for nonaqueous electrolyte secondary battery, negative electrode for nonaqueous electrolyte secondary battery, nonaqueous electrolyte secondary battery, and method for manufacturing negative electrode material for nonaqueous electrolyte secondary battery

    JP2016164870A

  • Negative electrode material for battery, method for manufacturing the same, negative electrode for secondary battery, and secondary battery

    JP2019125435A

  • Silicon nanoparticles, active material for negative electrode of non-aqueous secondary battery including the same, and secondary battery

    JP2021114483A